2016
DOI: 10.1002/14651858.cd009077.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions for treating heart failure in patients with Chagas cardiomyopathy

Abstract: The results were inconclusive that carvedilol reduced all-cause mortality or improved quality of life more than placebo. The safety profile of carvedilol for Chagas cardiomyopathy remains unclear. One study assessed the e ect of rosuvastatin versus placebo, but did not show an e ect size. Therefore, the results from available clinical trials neither support nor reject the use of carvedilol or rosuvastatin in treating this clinical entity. Further investigation is warranted to investigate the exact applicabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…However, the recommended full doses of these drugs are often not reached, as patients with CHD have a high prevalence of atrioventricular block and autonomic nervous system disorders. Carvedilol is the most frequently used beta-blocker in CHD, although the quality of evidence is low and based on a meta-analysis that included 69 participants and found a lower all-cause mortality in the carvedilol group than in the placebo group[ 96 ].…”
Section: Heart Failurementioning
confidence: 99%
“…However, the recommended full doses of these drugs are often not reached, as patients with CHD have a high prevalence of atrioventricular block and autonomic nervous system disorders. Carvedilol is the most frequently used beta-blocker in CHD, although the quality of evidence is low and based on a meta-analysis that included 69 participants and found a lower all-cause mortality in the carvedilol group than in the placebo group[ 96 ].…”
Section: Heart Failurementioning
confidence: 99%
“…Although evidence is scant regarding the use of dual angiotensin receptor and neprilysin inhibitors (ARNI) and sodium-glucose transporter 2 inhibitors (SGLT-2), clinical trials are currently ongoing given the fact that approximately 7.6% of patients enrolled in the PARADIGM-HF, and the ATMOSPHERE trials, were diagnosed with Ch-CMP. Both medications are promising options for the treatment of Ch-CMP, an otherwise often refractory and highly morbid cause of heart failure [167][168][169][170]. Likewise, SCD prevention is based in the insertion of an implantable cardiac defibrillator and amiodarone therapy [171][172][173].…”
Section: Clinical Manifestations Diagnosis and Treatmentmentioning
confidence: 99%
“…Three trials evaluating carvedilol in ChCM were identified, with a total of 108 participants. [84] A lower proportion of all-cause mortality was found in the carvedilol groups compared with the placebo groups (RR 0.69; 95% CI [0.12–3.88]), with no difference in hospital readmissions. However, the authors found that the available evidence was low quality and there were no conclusive data to support or reject the use of carvedilol.…”
Section: Drug Heart Failure Management: Similar or Different?mentioning
confidence: 99%